2021
DOI: 10.1155/2021/2112814
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of a Tritrophic Leslie-Gower Food-Web System with the Effect of Fear

Abstract: The avoidance strategy of prey to predation and the predation strategy for predators are important topics in evolutionary biology. Both prey and predators adjust their behaviors in order to obtain the maximal benefits and to raise their biomass for each. Therefore, this paper is aimed at studying the impact of prey’s fear and group defense against predation on the dynamics of the food-web model. Consequently, in this paper, a mathematical model that describes a tritrophic Leslie-Gower food-web system is formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…However, the presence of a predator may drastically alter the prey's physiological and behavioral characteristics to the point where it may have a greater impact on the prey population than direct predation [17] and the mentioned references therein. There are many research studies using mathematical modeling considered the impact of hunting cooperation [1,[17][18][19][20][21][22][23][24][25] and the impact of fear [16,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] in the prey-predator models separately. Numerous prey species alter their behavior when predators are around because of the possibility of being eaten.…”
Section: Introductionmentioning
confidence: 99%
“…However, the presence of a predator may drastically alter the prey's physiological and behavioral characteristics to the point where it may have a greater impact on the prey population than direct predation [17] and the mentioned references therein. There are many research studies using mathematical modeling considered the impact of hunting cooperation [1,[17][18][19][20][21][22][23][24][25] and the impact of fear [16,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] in the prey-predator models separately. Numerous prey species alter their behavior when predators are around because of the possibility of being eaten.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that prey-predator interactions can be stabilized by significant anti-predator reflexes. With fear, Maghool et al 14 built and investigated a tritrophic Leslie-Gower food-web system. Because of the prey group's protective capability, the Sokol-Howell type of function response is employed to describe the predation process.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in the indirect example, a predator's presence drastically alters the prey's behavior due to their dread of the threat of predation [30]. As a result, numerous studies have been conducted to comprehend how prey fear affects the dynamics of the prey-predator system, see [9,[31][32][33][34][35][36][37][38][39] and the references therein. Despite the aforementioned, this paper combines the effects of fear, disease, and harvest in a single prey-predator system.…”
Section: Introductionmentioning
confidence: 99%